GROJ1750-27: A neutron star far behind the Galactic Center switching into the propeller regime - Lutovinov AA; Tsygankov SS; Karasev DI; Molkov SV; Doroshenko V (OXFORD UNIV PRESS, 2025)
We report on analysis of properties of the X-ray binary pulsar GROJ1750-27 based on X-ray (Chandra, Swift, and Fermi/GBM), and near-infrared (VVV and UKIDSS surveys) observations. An accurate position of the source is determined for the first time and used to identify its infrared counterpart. Based on the VVV data we investigate the spectral energy distribution (SED) of the companion, taking into account a non-standard absorption law in the source direction. A comparison of this SED with those of known Be/X-ray binaries and early-type stars has allowed us to estimate a lower distance limit to the source at >12 kpc. An analysis of the observed spin-up torque during a giant outburst in 2015 provides an independent distance estimate of 14-22 kpc, and also allows to estimate the magnetic field on the surface of the neutron star at B similar or equal to (3.5-4.5) x 10(12) G. The latter value is in agreement with the possible transition to the propeller regime, a strong hint for which was revealed by Swift/XRT and Chandra. We conclude, that GROJ1750-27 is located far behind the Galactic Centre, which makes it one of the furthest Galactic X-ray binaries known.